Kinerja Kelompok Tani dalam Meningkatkan Produktivitas Usahatani Padi di Kecamatan Muara Belida Kabupaten Muara Enim - Malini, Henny; Anisah, Enfant Faza; Wahyuni, Reshi (Seminar Nasional Lahan Suboptimal, 2023)
Malini, H., Anisah, A.F., Wahyuni, R. (2023). Performance of farmers group association in increasing rice farming productivity in Muara Belida District Muara Enim Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 472-481).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Achieving productivity in rice farming cannot be separated from the performance of farmer groups. The research objective is to measure the combined performance of farmer groups in increasing the productivity of rice farming. Calculating productivity and analyzing the relationship between Kelompok Tani performance and rice farming productivity. The research method is a survey method. Determination of samples using a simple random method. The results of this research based on the total score of 50.9, the performance of the farmer group is with medium criteria. Average production is 5,181 kg/year/arable area. The productivity of rice farming ranges from 1000 kg/ha to 6500 kg/ha and the average productivity is 3,455 kg/year/ha. There is a significant relationship between the performance of farmer groups and the productivity of rice farming. The performance of the rice farmer group as a vehicle for learning classes, a vehicle for collaboration and as a production unit has a score of 50.9 with medium criteria. The average productivity of rice farming is 3,455 kg/ha/year. There is a positive and significant relationship between the performance of farmer groups and productivity with a correlation coefficient value of 0.385 with the criterion of medium closeness.